ANALYSIS OF THE MUZARA'AH CONTRACT IN THE PRODUCTION SHARING SYSTEM OF SHALLOT FARMING IN KETAPANG VILLAGE, KADEMANGAN DISTRICT, PROBOLINGGO - Amalia, Diana Rizky Amalia; Warsidi; Isma Swadjaja (JSE: Jurnal Sharia Economica, 2026)
This study analyzes the implementation of muzara'ah contracts in shallot farming in Ketapang Village, Kademangan District, Probolinggo City as a community empowerment effort. Using a qualitative descriptive approach with case studies, this research involved 20 respondents consisting of 10 landowners and 10 cultivating farmers through in-depth interviews, non-participant observation, and documentation. The results show that muzara'ah practices have been implemented generationally through a 90:10 profit-sharing pattern based on oral agreements grounded in trust and kinship values, where landowners provide land, seeds, fertilizers, and other agricultural inputs, while cultivating farmers contribute labor and some equipment. The implementation of muzara'ah contracts is substantially in accordance with Islamic economic law principles, fulfilling the pillars and conditions including aqidain (100%), ma'qud 'alaih (85%), ijab qabul (100%), timeframe (95%), and profit-sharing proportion (100%), as well as applying the principles of an-taradhin (mutual consent), proportional justice, maslahah (public interest), and ta'awun (mutual cooperation). The integration of muzara'ah concepts has contributed to community empowerment through the enabling dimension with average income ≥IDR 5,000,000 per season allowing basic needs fulfillment and children's education, the empowering dimension with 85% farmers reporting improved cultivation knowledge, 90% capable of cost analysis, and 60% involved in farmer groups, and the protecting dimension that protects cultivating farmers from crop failure losses borne entirely by capital owners. However, challenges remain including lack of formal documentation (100% oral agreements), limited access to capital (75%), price fluctuations (90%), limited access to modern agricultural technology (65%), and limited understanding of muamalah fiqh aspects (35%).